2010
DOI: 10.1161/hypertensionaha.110.150029
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II–Induced Vascular Smooth Muscle Cell Migration and Growth Are Mediated by Cytochrome P450 1B1–Dependent Superoxide Generation

Abstract: Abstract-Cytochrome P450 1B1, expressed in vascular smooth muscle cells, can metabolize arachidonic acid in vitro into several products including 12-and 20-hydroxyeicosatetraenoic acids that stimulate vascular smooth muscle cell growth. This study was conducted to determine whether cytochrome P450 1B1 contributes to angiotensin II-induced rat aortic smooth muscle cell migration, proliferation, and protein synthesis. Angiotensin II stimulated migration of these cells, measured by the wound healing approach, by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
88
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 73 publications
(90 citation statements)
references
References 42 publications
2
88
0
Order By: Relevance
“…Among many agents, including cytokines, Ang II, and growth factors, PDGF is considered to be a primary stimulator of VSMC migration and proliferation, acting on the PDGF‐β receptor in medial SMCs and leading to neointimal growth 7, 20. Ang II– and PDGF‐BB–induced VSMC migration and proliferation in vitro are mediated via generation of ROS 6, 21. Ang II stimulates ROS production in VSMCs via activation of nicotinamide adenine dinucleotide phosphate (NADPH oxidase), which is dependent on arachidonic acid (AA) 22.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Among many agents, including cytokines, Ang II, and growth factors, PDGF is considered to be a primary stimulator of VSMC migration and proliferation, acting on the PDGF‐β receptor in medial SMCs and leading to neointimal growth 7, 20. Ang II– and PDGF‐BB–induced VSMC migration and proliferation in vitro are mediated via generation of ROS 6, 21. Ang II stimulates ROS production in VSMCs via activation of nicotinamide adenine dinucleotide phosphate (NADPH oxidase), which is dependent on arachidonic acid (AA) 22.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have reported that Ang II–induced VSMC migration and proliferation are mediated by ROS generated from the metabolism of AA by CYP1B1, resulting in stimulation of ≥1 signaling molecules 6. In the present study, the PDGF‐BB–induced increase in ROS, measured as H 2 O 2 in VSMCs, and their migration and proliferation were attenuated by Cyp1b1 gene disruption and by Tempol, which does not alter CYP1B1 activity6 and inactivates superoxides as well as H 2 O 2 by superoxide dismutase– and catalase‐like actions, respectively 9. This suggested that these effects of PDGF‐BB are also dependent on CYP1B1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations